2010
DOI: 10.4049/jimmunol.0804051
|View full text |Cite
|
Sign up to set email alerts
|

Costimulator B7-DC Attenuates Strong Th2 Responses Induced by Nippostrongylus brasiliensis

Abstract: The caliber and magnitude of T cell responses are regulated by costimulatory molecules following the engagement of TCRs and MHC molecules. B7-DC has the highest homology with B7-H1 in the B7 family, and both of them bind an immunoregulatory molecule, programmed death 1. Previous studies have demonstrated that B7-DC stimulates T cell proliferation and CTL generation, which sharply contrasts the inhibitory role of B7-H1. Th2 cytokines prompt B7-DC expression, which in turn enhances Th1 responses. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…We found that PDL2 expression was stably associated with this DC subset (see below), and we will therefore refer to them here as PDL2 + DCs. Interleukin-4 (IL-4) is known to induce PDL2 expression on dendritic cells (Ishiwata et al, 2010). Interestingly, in vitro generation of PDL2 + DCs could be promoted by IL-4 and inhibited by transforming growth factor-β (TGF-β) (see Figure S1 Aavailable online).…”
Section: Resultsmentioning
confidence: 99%
“…We found that PDL2 expression was stably associated with this DC subset (see below), and we will therefore refer to them here as PDL2 + DCs. Interleukin-4 (IL-4) is known to induce PDL2 expression on dendritic cells (Ishiwata et al, 2010). Interestingly, in vitro generation of PDL2 + DCs could be promoted by IL-4 and inhibited by transforming growth factor-β (TGF-β) (see Figure S1 Aavailable online).…”
Section: Resultsmentioning
confidence: 99%
“…This result was similar to the findings of Shin and colleagues who used knockout mice to show that B7-DC enhances the Th1 response. 18,26 In addition, mB7-DC-Fc directly increases the proliferation of CD4 + but not CD8 + T cells. In contrast, mB7-DC-Fc increased tumor-specific CD8 + TILs in tumor bearing vaccinated mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, PD-1 may not be the only receptor for PD-L2. This can be inferred from helminth infection and allergic animal models, showing enhanced disease severity when PD-L2 blocking antibodies were used, but not when PD-1 blocking antibodies were used (47,48). Furthermore, PD-L2 mutants with abolished PD-1 binding capacity could still exert functional effects on T cells from normal and PD-1-deficient mice (49).…”
Section: Discussionmentioning
confidence: 99%